Pelatihan Desain Grafis untuk Meningkatkan Kompetensi Siswa SMKN 1 Padang Cermin - Donaya Pasha; Adi Sucipto; Jupriyadi Jupriyadi; Andi Nurkholis; Johansyah Johansyah; Muhammad Fauzan Ramadhani; Nadia Aftirah; Tia Nanda Pratiwi (Journal of Engineering and Information Technology for Community Service, 2023)
In this graphic design training, students are given material on introducing logos using the Corel Draw application, introducing the use of Adobe Photoshop to students being able to make flyers, banners, name cards, photo editing and cover books so that students have skills in using Adobe Photoshop. After participating in this Graphic Design Training, it is expected that participants will master the basic concepts of graphic design and digital design well, be able to design and utilize these various facilities in producing an artistic and communicative printed product creation, which has the main objective as a medium for conveying information, promotion and publication to the public. audience as the target.